eSports in times of a global pandemic: opportunities and future challenges when transforming gaming into a sport in Costa Rica - Rojas-Valverde, Daniel (Escuela de Educación Física y Deportes - Universidad de Costa Rica, 2020)
In response to the COVID-19 global pandemic, the world has undergone a series of drastic changes. Due to this, postponement and cancellation of multiple annual big sports events have been announced, giving way to new digital alternatives that follow government isolation provisions. eSports has shown to be a rapidly evolving alternative to maintain the sportsmanship and passion that sports bring to the general population. In Costa Rica, like everywhere else, this sport has seen accelerated growth with a high rate of evolution. In this regard, the country faces significant challenges to promote future eSports events, professional development, and the creation of an organizational structure for its optimal practice. This paper aims to analyze how the global pandemic exposes the need to direct the attention to digital sports alternatives such as eSport and the future challenges that Costa Rica will face to develop it in an effective and efficient way.